Peningkatan Kapabilitas Sistem Tindak Lanjut Rekomendasi BPK Inspektorat Utama BPS RI Melalui Pembangunan Sistem Informasi - Pradana, Novanni Indi; Maghfiroh, Lutfi Rahmatuti (Seminar Nasional Official Statistics, 2024)
Statistics Indonesia (BPS) prepares financial reports for budget accountability and submits them to the Audit Board of Indonesia (BPK) for review. The BPK audit results are presented in the audit report (LHP), and the Main Inspectorate directs the implementation of follow-up actions on BPK recommendations. Currently, a dashboard system monitors the progress and results of these follow-ups, but it does not cover the entire process, has limited access, and lacks centralized documentation storage. To address these issues, a new information system is needed. The proposed system was developed using the iterative method and evaluated with black box testing and the Computer System Usability Questionnaire (CSUQ). The black box testing results indicate that the system functions as expected. Additionally, the CSUQ evaluation shows high user satisfaction with the system's usability, information quality, and interface.